Multimodality during fixation - Part II: Evidence for multimodality in spatial precision-related distributions and impact on precision estimates - Lee Friedman; Timothy Hanson; Oleg Komogortsev (Bern Open Publishing, 2021)
This paper is a follow-on to our earlier paper (Friedman, Lohr, Hanson, & Komogortsev, 2021), which focused on the multimodality of angular offsets.  This paper applies the same analysis to the measurement of spatial precision.  Following the literature, we refer these measurements as estimates of device precision, but, in fact, subject characteristics clearly affect the measurements.  One typical measure of the spatial precision of an eye-tracking device is the standard deviation (SD) of the position signals (horizontal and vertical) during a fixation.  The SD is a highly interpretable measure of spread if the underlying error distribution is unimodal and normal. However, in the context of an underlying multimodal distribution, the SD is less interpretable. We will present evidence that the majority of such distributions are multimodal (68-70% strongly multimodal).  Only 21-23% of position distributions were unimodal. We present an alternative method for measuring precision that is appropriate for both unimodal and multimodal distributions.  This alternative method produces precision estimates that are substantially smaller than classic measures.  We present illustrations of both unimodality and multimodality with either drift or a microsaccade present during fixation.  At present, these observations apply only to the EyeLink 1000, and the subjects evaluated herein.